The Origins of Language: An Introduction to Evolutionary Linguistics - Francis, Norbert (Verbum, 2024)
Joanna DORNBIERER-STUART. The origins of language: An introduction to evolutionary linguistics, New York, Palgrave Macmillan, 2024, 188 p.